2012
DOI: 10.1364/boe.3.000899
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced localized plasmonic detections using partially-embedded gold nanoparticles and ellipsometric measurements

Abstract: A cost-effective, stable and ultrasensitive localized surface plasmon resonance (LSPR) sensor based on gold nanoparticles (AuNPs) partially embedded in transparent substrate is presented. Partially embedded AuNPs were prepared by thermal annealing of gold thin films deposited on glass at a temperature close to the glass transition temperature of the substrate. Annealed samples were optically characterized by using spectroscopic ellipsometry and compare with theoretical modeling to understand the optical respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…4b. In the case of unmodified plate, AuNPs were not adsorbed on the surface (Moirangthem et al 2012;Carré and Lacarrière 2007;Fujiwara et al 2006). Figure 5a, b shows that the AuNPs stained modified and unmodified GS surface, respectively.…”
Section: Synthesis and Characterization Of Citrate-capped Aunpsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b. In the case of unmodified plate, AuNPs were not adsorbed on the surface (Moirangthem et al 2012;Carré and Lacarrière 2007;Fujiwara et al 2006). Figure 5a, b shows that the AuNPs stained modified and unmodified GS surface, respectively.…”
Section: Synthesis and Characterization Of Citrate-capped Aunpsmentioning
confidence: 99%
“…Covalent immobilization of biomolecules on PS and GS surfaces can be achieved using a variety of techniques including wet chemical treatments, silane monolayers, plasmas, flame, and UV irradiation (Goddard and Hotchkiss 2007). Among these, silane monolayer using 3-aminopropylyl triethoxy silane (APTES), 3-aminopropylyl trimethoxy silane (APTMS), N-[3-(trimethoxysilyl) propyl]ethylenediamine (TMSPED), and 3-glycidoxy propyl trimethoxy silane (GOPS) for the functionalization of the amine and the epoxy groups on the PS plate and the GS surfaces (Huang et al 2012;Moirangthem et al 2012;Wang and Vaughn 2008;Yang et al 2005;Lin et al 2006;Kobayashi et al 2007;Dixit et al 2011). APTES functionalized PS plates and GS are used in the immobilization of antibodies for the detection of antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Moirangthem et.al. [32] has presented ultrasensitive LSPR sensor based on AuNPs coated with anti-human epidermal growth factor receptor (anti-EGFR) and partially embedded in transparent substrate. The device was able to detect the receptor in concentrations as low as 20 pM.…”
Section: Figurementioning
confidence: 99%
“…Spectroscopic ellipsometry has been recently used for biosensing, in combination with plasmonics, whereby even small changes in optical properties produced by biofunctionalization or biorecognition can be detected and sometimes amplified [7,8]. Previous studies have shown that different polarization states of the light scattered and reflected by a sample can provide, with appropriate modeling, information about its optical properties, roughness and thickness [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that different polarization states of the light scattered and reflected by a sample can provide, with appropriate modeling, information about its optical properties, roughness and thickness [8][9][10]. In the context of scattering of light by a sphere placed on a surface, ellipsometric measurements are the most common and practical means of characterization.…”
Section: Introductionmentioning
confidence: 99%